Pregnancy Disease Diagnostic Expert System With Certainty Factor Method - Embun Fajar Wati; Elvi Sunita Perangin-Angin; Budi Sudrajat (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
Lack of knowledge and information about diseases in pregnancy can delay pregnant women from knowing there are diseases in their pregnancy. Diseases that attack a woman's womb need to be examined by an expert, while experts for this disease are still rare and require a lot of money. In order for the initial diagnosis to be carried out by pregnant women, a solution is proposed in the form of an expert system for diagnosing pregnant women's diseases using the Certainty Factor (CF) method based on the symptoms felt by pregnant women. The research stages used in this study used 4 steps, namely data collection consisting of disease data and symptom data, disease data and symptoms, as well as patient data, symptoms and weights, data analysis using the certainty factor method, validation and evaluation. Diagnostic results that are not in accordance with the CF calculation of around 37.5%, while the results in accordance with the CF calculation were 11 patients or 62.5%.